2014
DOI: 10.1186/1476-072x-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Spatial epidemiology of dry eye disease: findings from South Korea

Abstract: BackgroundDED rate maps from diverse regions may allow us to understand world-wide spreading pattern of the disease. Only few studies compared the prevalence of DED between geographical regions in non-spatial context. Therefore, we examined the spatial epidemiological pattern of DED prevalence in South Korea using a nationally representative sample.MethodsWe analyzed 16,431 Korean adults aged 30 years or older of the 5th Korea National Health and Nutrition Examination Survey. DED was defined as previously diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 41 publications
8
64
0
5
Order By: Relevance
“…This aspect of our results and the effects of seasonality in dry eye disease are strongly supported by a recent Korean study that identified a relationship between longer sunshine duration/lower humidity and the prevalence of DED (Um et al. ). This evidently emphasizes the importance of the principles of psychrometry considering the mixture of water vapour and air, because of its application in heating, ventilating, and air‐conditioning and meteorology.…”
Section: Discussionsupporting
confidence: 89%
“…This aspect of our results and the effects of seasonality in dry eye disease are strongly supported by a recent Korean study that identified a relationship between longer sunshine duration/lower humidity and the prevalence of DED (Um et al. ). This evidently emphasizes the importance of the principles of psychrometry considering the mixture of water vapour and air, because of its application in heating, ventilating, and air‐conditioning and meteorology.…”
Section: Discussionsupporting
confidence: 89%
“…An epidemiological study conducted in South Korea also showed the presence of dry eye symptoms being more prevalent in patients between 60 and 69 years. (18) A study of Aditya Rege also found a significant increase in the prevalence of dry eye in elderly patients. As in people under 40 years dry eye prevailed in 6.06% of men and 10.09% of women, in those over 60 years the prevalence was 26.28% and 31.72%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…This variation has been suggested to be influenced by geographical location, the variety of the population studied, variation in diagnostic criteria used with an observed lack of standard diagnostic criteria across all studied. In general, it was reported that prevalence of DED more prevalent in Asian countries compared to Western countries [13].…”
Section: Introductionmentioning
confidence: 95%